2014
DOI: 10.4067/s0034-98872014001100007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia y características de mutaciones somáticas del gen KRAS en pacientes chilenos con cáncer colorectal

Abstract: Prevalencia y características de mutaciones somáticas del gen KRAS en pacientes chilenos con cáncer colorrectalClaudia hurtado 1,a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Other studies in Latin America report contrasting frequencies ranging from 13% (Colombia and Venezuela) to 40% (Chile). However, the literature shows that the RAS mutation prevalence usually has a range of 26% to 50% [ 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in Latin America report contrasting frequencies ranging from 13% (Colombia and Venezuela) to 40% (Chile). However, the literature shows that the RAS mutation prevalence usually has a range of 26% to 50% [ 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Venezuela) to 40% (Chile). However, the literature shows that the RAS mutation prevalence usually has a range of 26% to 50% [34][35][36]. Previous studies have shown that mutations in KRAS are variable among populations.…”
Section: Plos Onementioning
confidence: 99%
“…CRC develops through a series of somatic gene mutations that promote malignant behavior [2]. These traditional pathway mutations, propagated by long-lived progenitor cells, lead to activation of proliferative signaling pathways, crypt fission, and aberrant glands that progress pathologically from aberrant crypt foci into small adenomatous polyps and ultimately invasive adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…34 Although the genetic term generally leads to understanding cancer as a hereditary disease, this only occurs in a small percentage. In most tumors, the alterations described are only somatic and, therefore, cannot be transmitted to offspring 35,36 so it is important to study mutations linked to cancers. Here we evidence 55 mutations in the 10 HMTs genes studied.…”
Section: Discussionmentioning
confidence: 99%